Pulmonary Embolism Presenting as ST-Elevation Myocardial Infarction: A Diagnostic Trap - Siddiqa, Ayesha (Am J Case Rep, 2020)
Patient: Male, 50-year-old Final Diagnosis: Submassive pulmonary embolism Symptoms: Chest pain • dyspnea Medication: — Clinical Procedure: Cardiac catheterization Specialty: Cardiology • Critical Care Medicine • Pulmonology OBJECTIVE: Challenging differential diagnosis BACKGROUND: The clinical presentation of pulmonary embolism (PE) is highly variable, ranging from no symptoms to shock or sudden death, often making the diagnosis a challenge. An electrocardiogram (EKG) is not a definitive diagnostic tool; however, it can alter the clinical suspicion of acute PE. PE has nonspecific electrocardiographic patterns ranging from a normal EKG in almost 33% of patients to sinus tachycardia, S1Q3T3 pattern (McGinn-White Sign), right axis deviation, and incomplete right bundle branch block (RBBB). ST-segment elevation associated with PE is exceedingly rare, and to date, only a few cases have been reported. CASE REPORT: We present a case of a middle-aged male patient with no medical comorbidities other than obesity, who presented with initial symptoms and EKG findings concerning an ST-elevation myocardial infarction (STEMI). He was later found to have rather patent coronary arteries on cardiac catheterization but bilateral sub-massive pulmonary embolism on computed tomography angiogram (CTA) of the chest. CONCLUSIONS: The differential diagnosis of STEMI is broad, including, but not limited to, Prinzmetal’s angina, takotsubo cardiomyopathy, Brugada syndrome, left ventricular aneurysm, hypothermia, hyperkalemia, and acute pericarditis. Pulmonary embolism may present with abnormal EKG and biomarkers that appear to be an acute coronary syndrome, even STEMI. Physicians must maintain a high index of clinical suspicion through risk stratification to identify PE in these settings, as the frequency of such an occurrence is extremely low. A bedside echocardiogram can be an invaluable diagnostic tool in such cases.